Environmentally Responsible Behavior of High School Students in terms of The Ability to Solve Environmental Problems - Karyati Karyati (Tadris Biologi, Tadris Fisika and Tadris Kimia, Universitas Islam Negeri Antasari, 2022)
This research aimed to determine whether there is a positive relationship between the ability to solve environmental problems with environmentally responsible behavior and to determine other factors that have a relationship with environmentally responsible behavior. The population of this study were students of SMAN 1 Arjawinangun. This research was conducted in March-May 2021. The quantitative research data were obtained by using questionnaires, and multiple choice. The qualitative research data were obtained by doing interviews and observations. The data hypothesis was tested using statistics SPSS version 26. The results of this research showed that there was a positive relationship between environmentally responsible behavior and the ability to solve environmental problems. The interpretation correlation coefficient value is very low and is influenced by other factors.